Preliminary study for improving nutritional status and anti-inflammatory effect of low-fat soymilk intake in elderly people - Kohno, Mitutaka; Yamamoto, Ai; Shintomi, Tamaki; Tomoe, Miki (Journal of the Japan Dietetic Association, 2021)
In this study, "low-fat soy milk (Fuji Oil Co., Ltd.)" was added to meals (miso soup) for two months for elderly people over 70 years old. We investigated the nutritional status improvement and anti-inflammatory effect of low-fat soy milk intake. This study was conducted from September to December 2014 with 17 elderly people living in carehouses as subjects. During the test meal intake period, 85 ml of low-fat soymilk (Fuji Oil Co., Ltd.) was added to miso soup for breakfast. The test items were body measurement, simple nutritional status assessment (MNA®-SF), food intake survey, and blood biochemistry test. Conducted with the approval of the Kyushu Women's University Ethics Review Committee. MNA®-SF showed significantly higher levels compared to the post-observation period than during the 8 week intake period, indicating maintaining nutritional status. Protein intake increased significantly during the intake period of 4 weeks and intake period of 8 weeks. The estimated glomerular filtration rate was not significantly different in the intake period 4 weeks and 8 weeks compared to the previous observation period. TNF-α was significantly lower in the intake period 8 weeks than in the previous and subsequent observation periods. Ingestion of low-fat soy milk enabled protein administration to elderly people over 70 years of age without burdening the kidney, and was thought to contribute to the maintaining nutritional status and the anti-inflammatory effect due to TNF-α lowering action.